Audit on public buildings by National Audit Department and public works department: a process overview - Ariffin, Khadijah Md; Juanil, David Martin @ Daud; Kasim, Rozilah (American Scientific Publishers, 2018)
Audit on Public Buildings (PBs) is relatively new in Malaysia. In view of this, the processes involved in the audit on PBs are still unclear. This research has identified two departments, namely the National Audit Department (NAD) and Public Works Department (PWD) as the departments which conduct audit on PBs in Malaysia. Thus, this study was aimed to compare the processes involved in the audit by both NAD and PWD. Data were collected through interviews and document reviews and analyzed using thematic data analysis. The findings revealed the approach and methodology selected for the assessment for both departments vary accordingly to its aim and purpose of audit.